2019
DOI: 10.9734/jaeri/2019/v19i430088
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Risk Factors of Cow Mastitis among Small Scale Farmers and Dairy Farms in Western Tigray, Northwest Ethiopia

Abstract: A cross sectional study was carried out from November 2017 to June 2018 to assess awareness status and management practice common among dairy cows owners and to determine the prevalence of bovine mastitis and its associated risk factors in four districts and nine kebelles of Western Zone of Tigray Regional State, North West Ethiopia. In this study, out of the 355 dairy cows and 1314 functional quarters examined, 99(27.89%) cows and 142(10.81%) quarters were found positive for sub-clinical mastitis on Californi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Additionally, depression is associated with community discrimination, with orphans experiencing discrimination being 2.68 times more likely to develop depression. This fi nding is consistent with similar studies in India [37], potentially stemming from the isolating eff ect of perceived societal exclusion.…”
Section:  Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, depression is associated with community discrimination, with orphans experiencing discrimination being 2.68 times more likely to develop depression. This fi nding is consistent with similar studies in India [37], potentially stemming from the isolating eff ect of perceived societal exclusion.…”
Section:  Discussionsupporting
confidence: 92%
“…Additionally, research has highlighted that orphaned individuals with low social support, experiences of discrimination, and lack of biological relatives are more susceptible to depressive disorders [36][37][38][39]. A 2013 study conducted in Mekelle, Ethiopia, found signifi cant associations between depressive disorder and community and peer discrimination [40].…”
mentioning
confidence: 99%
“…P.aeruginosa 4(2.99%) prevalence reported in this study also less than [37] who reported relative prevalence of 5(4.1%) whereas proteus species. with 7(5.22%) prevalence reported in this study higher than [10,37] who reported 2(2.7%) and 1(1.9%) prevalence respectively (Table 2). Characteristics of pathogens, environmental condition and level of management to risk factor which influence the prevalence of mastitis could be the reason for these differences in occurrence [23].…”
Section: Bacteriological Examinationcontrasting
confidence: 53%